No pain, still gain (of function): the relation between sensory profiles and the presence or absence of self-reported pain in a large multicenter cohort of patients with neuropathy. Issue 3 (March 2021) - Forstenpointner, Julia; Ruscheweyh, Ruth; Attal, Nadine; Baron, Ralf; Bouhassira, Didier; Enax-Krumova, Elena K.; Finnerup, Nanna B.; Freynhagen, Rainer; Gierthmühlen, Janne; Hansson, Per; Jensen, Troels S.; Maier, Christoph; et al.
Abstract : Abstract: The pathophysiology of pain in neuropathy is complex and may be linked to sensory phenotypes. Quantitative sensory testing, a standardized method to evaluate sensory profiles in response to defined stimuli, assesses functional integrity of small and large nerve fiber afferents and central somatosensory pathways. It has revealed detailed insights into mechanisms of neuropathy, yet it remains unclear if pain directly affects sensory profiles. The main objective of this study was to investigate sensory profiles in patients with various neuropathic conditions, including polyneuropathy, mononeuropathy, and lesions to the central nervous system, in relation to self-reported presence or absence of pain and pain sensitivity using the Pain Sensitivity Questionnaire. A total of 443 patients (332 painful and 111 painless) and 112 healthy participants were investigated. Overall, loss of sensation was equally prevalent in patients with and without spontaneous pain. Pain thresholds were equally lowered in both patient groups, demonstrating that hyperalgesia and allodynia are just as present in patients not reporting any pain. Remarkably, this was similar for dynamic mechanical allodynia. Hypoalgesia was more pronounced in painful polyneuropathy, whereas hyperalgesia was more frequent in painful mononeuropathy (compared with painless conditions). Self-reported pain sensitivity was significantly higher in painful than in painless neuropathic conditions. Our results reveal the presence of hyperalgesia and allodynia in patients with central and peripheral lesions of the somatosensory system not reporting spontaneous pain. This shows that symptoms and signs of hypersensitivity may not necessarily coincide and that painful and painless neuropathic conditions may mechanistically blend into one another. Abstract : Supplemental Digital Content is Available in the Text.Sensory testing reveals allodynia and hyperalgesia in painless neuropathic conditions in a similar frequency to painful neuropathic conditions